Learning Society in Accelerating the Increase of English Understanding and Communicating at Mahesa Putri English Camp - Yulianingsih, Wiwin; Lestari, Gunarti Dwi; Dewi, Utari; Rahma, Rezka Arina (Journal of Nonformal Education, 2021)
Camp is one form of non-formal education that is used as a place to live while undergoing language courses. This study is generally aimed at determining the learning society in accelerating the improvement of understanding skills and communication skills in a camp-based English course for students in Mahesa Putri Camp in English Village. The purpose of this study is to determine the role of camp as an enhancer of understanding ability, and the role of camp as an acceleration of communication patterns. The research method used is descriptive qualitative which describes something objectively, based on data analysis conducted at the time of data collection and after data collection. Data collection techniques used were observation, interviews and documentation. In this study, the subjects of the study were managers, tutors and students at Mahesa Putri Camp English Village Pare, Kediri. From the results of the study, it was found that the students experienced an increase in understanding of learning and motivation from activities in the campThe importance of this research to provide and understanding of the existence of camp provides an acceleration in learning english.